EFFECT SIGNIFICANCE ASSESSMENT OF THE THERMODYNAMICAL FACTORS ON THE SOLID OXIDE FUEL CELL OPERATION - V. A. Sednin; A. A. Chichko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
Technologies of direct conversion of the fuel energy into electrical power are an upcoming trend in power economy. Over the last decades a number of countries have created industrial prototypes of power plants on fuel elements (cells), while fuel cells themselves became a commercial product on the world energy market. High electrical efficiency of the fuel cells allows predictting their further spread as part of hybrid installations jointly with gas and steam turbines which specifically enables achieving the electrical efficiency greater than 70 %. Nevertheless, investigations in the area of increasing efficiency and reliability of the fuel cells continue. Inter alia, research into the effects of oxidizing reaction thermodynamic parameters, fuel composition and oxidation reaction products on effectiveness of the solid oxide fuel cells (SOFC) is of specific scientific interest. The article presents a concise analysis of the fuel type effects on the SOFC efficiency. Based on the open publications experimental data and the data of numerical model studies, the authors adduce results of the statistical analysis of the SOFC thermodynamic parameters effect on the effectiveness of its functioning as well as of the reciprocative factors of these parameters and gas composition at the inlet and at the outlet of the cell. The presented diagrams reflect dimension of the indicated parameters on the SOFC operation effectiveness. The significance levels of the above listed factors are ascertained. Statistical analysis of the effects of the SOFC functionning process thermodynamical, consumption and concentration parameters demonstrates quintessential influence of the reciprocative factors (temperature – flow-rate and pressure – flow-rate) and the nitrogen N2 and oxygen O2 concentrations on the operation efficiency in the researched range of its functioning. These are the parameters to be considered on a first-priority basis while developing mathematical models for optimizing the solid oxide fuel cells operating modes.